Corporate social responsibility practices among the SMEs in Malaysia - a preliminary analysis / Norhafizah Norbit, Anuar Nawawi and Ahmad Saiful Azlin Puteh Salin. - Norbit, Norhafizah; Nawawi, Anuar; Puteh Salin, Ahmad Saiful Azlin (Accounting Research Institute (ARI, Universiti Teknologi MARA, Shah Alam, 2017)
There are four main objectives of this study. First, to examine the level of CSR practice in selected Malaysian small and medium enterprises (SMEs). Second, to determine the motivation of implementing CSR practices. Third, to determine the barriers on the implementation of CSR practices. Finally, to examine the attitude of twenty selected Malaysian SMEs owners towards CSR practice. This study employed a mixed method in data collection and analysis via survey questionnaires to the selected SMEs and archival analysis by examining the financial reports of those SMEs. This study found that SMEs is still lag behind in implementing CSR practices. Although they understand the benefits such as enhancing company’s reputation and promote brand name, limited fund available and proper training required prevent them to implement effective CSR practices. This study also found that the SMEs’ owners have a positive attitude on CSR practices.